Aesthetic Problems of Revalorization of the Architectural Environment of the Paths and Nodes of the "Small Center" of the City of Yerevan - Sahakyan, Mesrop (Scientific Papers of National University of Architecture and Construction of Armenia, 2023)
The article considers the problems of the aesthetic revalorization of the architectural-spatial environment of the "Small Center" of Yerevan. The physical forms related to the image content, particularly the paths and nodes, which are part of the main objects of aesthetic revalorization, have been distinguished and studied. The types of these objects were coordinated and classified according to their meaning and function. The mutual arrangement of objects, their interconnection, co-subordination were revealed and evaluations were given according to the criteria of the value of the object, which serves as a basis for the identification of the main problems of aesthetic revalorization, for developing recommendations and models.